Vitamin A is associated with all-cause mortality in patients with chronic kidney disease: a population-based cohort study - Feng, Yunxia; Li, Yuan; Chen, Shuo; Hu, Na; Liao, Dan (Frontiers in Nutrition, 2024)
The association between serum vitamin A (VA) levels and outcomes in chronic kidney disease (CKD) patients remains unclear.This was a population-based cohort study. CKD participants from the National Health and Nutrition Examination Survey (NHANES) database were included for analysis. The primary outcome was all-cause mortality. Person correlation analysis and Cox regression models were used to assess the relation between serum VA levels and all-cause mortality among individuals with CKD.Results: There were 689 participants included in this study. The serum VA level was 2.45 ± 1.06 μmol/L. The overall mortality was 43.69%. The participants in the nonsurvival group had higher serum VA levels than those in the survival group (2.18 ± 0.82 vs. 2.78 ± 1.24 μmol/L, p < 0.01). Serum VA concentrations were positively correlated with serum creatinine levels (r = 0.56, p < 0.01) and urea nitrogen (r = 0.58, p < 0.01) but negatively correlated with eGFR (r = -0.56, p < 0.01). The serum VA level was independently related to all-cause mortality (hazard ratio (HR) = 1.15, [95% CI: 1.01-1.31], p = 0.03). The Kaplan-Meier survival analysis suggested that the survival probability was lower in participants with serum VA levels exceeding 2.09 μmol/L than in participants with serum VA levels below 2.09 μmol/L (p < 0.0001).A high serum VA was independently related to all-cause mortality in CKD patients. VA requirements for patients with CKD is worth studies in the future.